Adam's curse : a future without men - Sykes, Bryan (Norton & Co., 2004)
"Bryan Sykes, already one of the world's preeminent geneticists, established himself as one of science's most fascinating explicators of the mysteries of human origins. Now, in Adam's Curse, he returns with an equally spellbinding volume that examines the perilous future of the Y chromosome and the ultimate survival of men. So dire is this situation, Sykes demonstrates, that the day will come, perhaps 125,000 years from now, when the Y chromosome could literally cease to exist.".